The influence of Continuing Professional Development (CPD) lectures on referrals in the medical profession - Rammile, Nthabeleng (University of the Free State, 2005)
The purpose of CPD lectures is to provide learning on a continuous basis to keep medical doctors up to date with the newest scientific developments. The major responsibility of CPD provision is to address two interrelated tasks, namely to sustain motivation among established general practitioners (GP’s) and specialists for self-directed learning based on experience and to device ways of sharing individual experiences. In the process of fulfilling these two tasks, CPD lectures can also be utilized as a marketing tool for both the hospital and the specialist. This means that the specialist, in the process of presenting the lecture, can utilise this platform to market his/her expertise and the resources of the hospital from where he functions so as to increase the number of referrals he/she receives. Consultation and referrals have always been important processes for both the GP’s and specialists. It is of the utmost importance for specialists to establish networks with the GP’s in order to establish a stable referral pattern. It is however also important that this network pattern grows due to the fact that competition for patients intensifies and because more and more health care organisations are devoting more resources to understand the factors that directly or indirectly influence patient volume. Once these factors are identified, it will be easier to influence patient volume for the benefit of the hospital and the specialist.
Dissertation (M.P.L. (Business Management))--University of the Free State, 2005
Keywords: Medical referral; Communication in marketing; Customer services; Physicians -- Education(Continuing education)